Confounders in the detection of minimal hepatic encephalopathy: a neuropsychological and quantified EEG study. (23rd July 2014) - Campagna, Francesca; Montagnese, Sara; Schiff, Sami; Ruzzoli, Manuela; Biancardi, Anna; Iannizzi, Pamela; Pujatti, Pietro L.; Angeli, Paolo; Gatta, Angelo; Merkel, Carlo; Leandro, Gioacchino; Mapelli, Daniela; et al.
Abstract Background & Aims Chronic alcohol misuse, HCV infection and cirrhosis may cause cognitive alterations. The aim of the present study was to assess the influence of alcohol misuse, HCV infection and cirrhosis per se on the neuropsychological and electroencephalogram (EEG) profile and to evaluate the role of alcohol misuse and HCV infections as potential confounding factors in the detection of minimal hepatic encephalopathy. Methods A comprehensive neuropsychological profile and EEG spectral parameters were obtained in six age‐matched groups of 30 subjects each: (i) HCV‐related hepatitis without cirrhosis, (ii) chronic alcohol abusers, (iii) patients with HCV‐related cirrhosis, (iv) alcohol‐related cirrhosis, (v) cirrhosis not related to alcohol or HCV and (vi) healthy subjects. Cirrhotic patients were matched for MELD score. Results The factor 'cirrhosis' was associated with low Phonemic Verbal Fluency (PVF) and Difference between Trail Making Test B and A (TMT) (B‐A) (P < 0.001). Chronic alcohol misuse was associated with low PVF, TMT (B‐A), Memory with Interference Task at 10 (ITM 10) and 30 s (ITM 30) (all P < 0.05). An interaction was found between the factors 'cirrhosis', 'alcohol misuse' and tests (P < 0.01). HCV hepatitis reduced ITM 10 (P < 0.05), but no interaction was found between 'cirrhosis', 'HCV infection' and tests (P = 0.14). The EEG parameters were mainly influenced by 'cirrhosis' (P < 0.05), and EEG alterations were more pronounced in patients with alcoholic cirrhosis (P = 0.04). Conclusions Cirrhosis per se, chronic alcohol misuse and HCV infection were found to be associated with cognitive dysfunction. In patients with cirrhosis, the interaction with alcohol misuse further impinged on brain dysfunction.